Comparing the value revelance of R&D reporting in Germany: standard and selection effects - Fred Ramb; Markus Reitzig (Deutsche Bundesbank, 2005)
On the basis of accounting and market data for firms and groups listed on German stock exchanges between 1997 and 2003, we show that the value relevance of R&D information under German accounting standards can be superior to that provided by US-GAAP and IAS. The results, obtained while dynamically controlling for partial freedom of firms to choose a standard in a modified Q model, show that the risk of IAS/US-GAAP misinforming investors during "bear market" periods is more relevant than their comparative advantage over the prudence principle of the German Commercial Code in "bull market" periods. Using the approach chosen for this study, it is possible not only to draw a clear dividing line between standard and selection effects but also to disentangle them along theoretical lines more clearly than in earlier studies.
Keywords: K11; M41; D82; M40; 330; Accounting standards; standard selection; R&D; value relevance; Germany; Industrielle Forschung; Berichtswesen; Informationswert; Bilanzrecht; Vergleich; Deutschland; USA; Welt